Mrs. Dalloway - Woolf, Virginia, 1882-1941 (Salt Lake City, UT : Project Gutenberg, 2023)
"Mrs. Dalloway" by Virginia Woolf is a novel published in 1925. It follows a single day in the life of Clarissa Dalloway, an upper-class woman in post-World War I London, as she prepares to host an evening party. Through stream of consciousness narration, the story weaves between present moments and memories, exploring Clarissa's past relationships and choices. A parallel narrative follows Septimus Warren Smith, a war veteran struggling with trauma, whose fate will unexpectedly touch Clarissa's world by day's end. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mrs_Dalloway
Release date is 2023-10-13
Carla Foust, Emmanuel Ackerman and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: London (England) -- Fiction; Psychological fiction; Domestic fiction; Married women -- Fiction; Triangles (Interpersonal relations) -- Fiction; Suicide victims -- Fiction; Middle-aged women -- Fiction